Assessing protected area vulnerability to climate change in a case study of South African national parks. Issue 5 (1st June 2022) - Coldrey, Kevin M.; Turpie, Jane K.; Midgley, Guy; Scheiter, Simon; Hannah, Lee; Roehrdanz, Patrick R.; Foden, Wendy B.
Abstract: Climate change is challenging the ability of protected areas (PAs) to meet their objectives. To improve PA planning, we developed a framework for assessing PA vulnerability to climate change based on consideration of potential climate change impacts on species and their habitats and resource use. Furthermore, the capacity of PAs to adapt to these climate threats was determined through assessment of PA management effectiveness, adjacent land use, and financial resilience. Users reach a PA‐specific vulnerability score and rank based on scoring of these categories. We applied the framework to South Africa's 19 national parks. Because the 19 parks are managed as a national network, we explored how resources might be best allocated to address climate change. Each park's importance to the network's biodiversity conservation and revenue generation was estimated and used to weight overall vulnerability scores and ranks. Park vulnerability profiles showed distinct combinations of potential impacts of climate change and adaptive capacities; the former had a greater influence on vulnerability. Mapungubwe National Park emerged as the most vulnerable to climate change, despite its relatively high adaptive capacity, largely owing to large projected changes in species and resource use. Table Mountain National Park scored the lowest in overall vulnerability. Climate change vulnerability rankings differed markedly once importance weightings were applied; Kruger National Park was the most vulnerable under both importance scenarios. Climate change vulnerability assessment is fundamental to effective adaptation planning. Our PA assessment tool is the only tool that quantifies PA vulnerability to climate change in a comparative index. It may be used in data‐rich and data‐poor contexts to prioritize resource allocation across PA networks and can be applied from local to global scales. Abstract : Resumen: El cambio climático es un gran obstáculo para que las áreas protegidas (AP) logren sus objetivos. Para mejorar la planeación de las AP, desarrollamos un marco de trabajo para evaluar la vulnerabilidad de estas ante el cambio climático con base en la consideración de los impactos potenciales del cambio climático sobre las especies, sus hábitats y los recursos que usan. Además, determinamos la capacidad de las AP para adaptarse a estas amenazas climáticas mediante la valoración de las categorías efectividad de la gestión de las AP, las tierras adyacentes y la resiliencia económica. Los usuarios logran un puntaje y clasificación de vulnerabilidad específicas de la AP con base en las calificaciones de estas categorías. Aplicamos el marco de trabajo a los 19 parques nacionales de Sudáfrica. Ya que todos los parques se manejan como una red nacional, exploramos cómo pueden asignarse de mejor manera los recursos para lidiar con el cambio climático. Se estimaron la importancia de cada parque para la conservación de la biodiversidad de la red y la generación de ganancias. Después usamos las estimaciones para sopesar los puntajes y las clasificaciones generales de vulnerabilidad. Los perfiles de vulnerabilidad de los parques mostraron combinaciones distintivas de impactos potenciales del cambio climático y capacidades de adaptación; los impactos tuvieron una mayor influencia sobre la vulnerabilidad. El Parque Nacional Mapungubwe se ubicó como el más vulnerable ante el cambio climático, a pesar de tener una capacidad de adaptación relativamente alta, principalmente debida a grandes cambios proyectados para el uso de recursos y especies. El Parque Nacional Table Mountain tuvo el puntaje más bajo de vulnerabilidad generalizada. Las clasificaciones de vulnerabilidad al cambio climático difirieron notablemente una vez que se aplicaron los factores de importancia; el Parque Nacional Kruger fue el más vulnerable bajo ambos escenarios de importancia. La evaluación de vulnerabilidad al cambio climático es fundamental para la planeación efectiva de la adaptación. Nuestra herramienta de valoración de las AP es la única que cuantifica la vulnerabilidad de las AP al cambio climático en un índice comparativo. Puede usarse en contextos con muchos o pocos datos para priorizar la asignación de recursos en las redes de AP y puede aplicarse desde la escala local hasta la mundial. 利用南非国家公园的案例研究评估保护区对气候变化的脆弱性: 【摘要】 气候变化使保护区实现保护目标面临挑战。为了改进保护区规划, 我们开发了一个框架, 在考虑气候变化对物种及其栖息地和资源利用潜在影响的基础上, 评估保护区对气候变化的脆弱性。我们还通过评估保护区管理有效性、邻近的土地使用情况和财政稳健性确定了保护区适应气候威胁的能力。使用者根据对这些类别的打分, 获得针对保护区的脆弱性得分和排名。本研究将该框架应用于南非的19个国家公园。由于这些国家公园是作为一个国家网络来管理的, 我们探讨了如何最好地分配资源以应对气候变化。我们还估计了每个国家公园对网络的生物多样性保护和创收的重要性, 并加权计算了其整体的脆弱性得分和排名。国家公园的脆弱性情况展现出不同气候变化潜在影响和适应能力的组合, 前者对脆弱性的影响更大。马蓬古布韦国家公园尽管适应能力相对较强, 但却最容易受到气候变化影响, 主要是由于其物种和资源使用方面预计会发生巨大变化。桌山国家公园的总体脆弱性得分最低。如果采用重要性加权, 则气候变化脆弱性的排名会出现明显变化;克鲁格国家公园在两种重要性情境下都是最脆弱的。气候变化脆弱性评估是有效的适应性规划的基础。我们的保护区评估工具是目前用比较指数量化保护区对气候变化脆弱性的唯一工具。它适用于数据充足和数据匮乏的情况, 可以确定保护区网络资源分配的优先次序, 并可用于从局部到全球的不同尺度。【翻译: 胡怡思; 审校: 聂永刚】